Uganda : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2019)
This Selected Issues paper tries to answer the question of how to promote employment in Uganda. It also discusses key stylized facts including labor market challenges, an overview of the labor market, and employment characteristics. Although issues relating to the determinants of employment are gaining momentum in Uganda, the literature is largely based on economic reports and qualitative studies. Uganda has implemented some social programs aimed at creating employment specifically for youth and women, though coverage is limited. These programs aim at providing an enabling environment for the private sector to create jobs and build the skills and requisite knowledge to make youth and women more employable. The existing social programs are good initiatives to address some of the labor market issues, though their coverage remains limited with funding constraints identified as one of the main challenges. Creating quality jobs will require comprehensive policies to promote headline growth and ensure inclusive growth, including measures to improve education and address challenges in gender and youth.